The 1956 Hungarian revolution : a history in documents - Békés, Csaba; Byrne, Malcolm; Rainer, M. János. (Budapest ; New York : Central European University Press, 2002)
If there had been all-news television channels in 1956, viewers around the world would have been glued to their sets between October 23 and November 4. This book tells the story of the Hungarian Revolution in 120 original documents, ranging from the minutes of the first meeting of Khrushchev with Hungarian bosses after Stalin's death in 1953 to Yeltsin's declaration made in 1992. Other documents include letters from Yuri Andropov, Soviet Ambassador in Budapest during and after the revolt. The great majority of the material appears in English for the first time, and almost all come from archives that were inaccessible until the 1990s.
Cover -- Series title page -- Title page -- Copyright page -- CONTENTS -- Preface by Árpád Göncz -- Foreword by Charles Gati -- Introductory Essay by Timothy Garton Ash -- Editors' Introduction and Acknowledgements -- Acronyms and Abbreviations -- Chronology of Events -- PART ONE HUNGARY BEFORE THE REVOLUTION -- PART TWO FROM DEMONSTRATIONS TO REVOLUTION -- PART THREE HUNGARY IN THE AFTERMATH -- DOCUMENTARY EPILOGUE -- Main Actors -- Organizations -- Bibliography -- Index -- Maps -- Pohoto gallery -- back cover
Includes bibliographical references (pages 568-582) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Hungary -- History -- Revolution, 1956 -- Sources; Soviet Union -- Foreign relations -- 1953-1975 -- Sources; Central Europe; Regions & Countries -- Europe; History & Archaeology; Hongrie -- Histoire -- 1956 (Révolution) -- Sources; URSS -- Relations extérieures -- 1953-1975 -- Sources; HISTORY; HISTORY -- Modern -- 20th Century; Soviet Union -- Foreign relations -- 1953-1975.; Hungary -- History -- Revolution, 1956.; Powstanie węgierskie (1956); Diplomatic relations; Hungary; Soviet Union; 1953-1975; 1956 Revolution, Cold War, Diplomacy, Foreign relations, Political violence, Sources, Soviet Union; Źródła historyczne; Źródła historyczne; History; Sources